Asupan kalsium, vitamin d, dan pengetahuan dengan faktor risiko osteoporosis pada wanita pra lansia dan lansia di Bangunjiwo Yogyakarta - Agustina, Liana; Fayasari, Adhila (UHAMKA PRESS, 2025)
Osteoporosis commonly occurs among pre-elderly and elderly women, characterized by decreased bone mass and changes in the microarchitecture of bone tissue, leading to bone fragility and an increased risk of fractures. The study aimed to analyze the association between calcium intake, vitamin D intake, and osteoporosis-related knowledge with the risk of osteoporosis among pre-elderly and elderly women. A cross sectional study was conducted involving 127 pre-elderly and elderly women in Bangunjiwo, Bantul, selected through purposive sampling. Data collected included subject characteristics, calcium, and vitamin D intake (measured using a Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ)), osteoporosis knowledge (measured using a structured questionnaire), and osteoporosis risk (assessed using the OPAQ-PF questionnaire). Data were analyzed using the chi-square test with a significance level of α<0,05. The results showed that more than 90% of both pre-elderly and elderly subjects were at risk of osteoporosis. A significant association was found between calcium intake and osteoporosis risk (p<0,001), as well as between knowledge and osteoporosis risk (p=0,041). However, no significant association was found between vitamin D intake and osteoporosis risk (p=0,071). In conclusion, this study identified calcium intake and knowledge as factors associated with the risk of osteoporosis among pre-elderly and elderly women, while vitamin D intake was not significantly associated with osteoporosis risk.